Tripleglow / Nazia Zulaiqha Nor Azlan ... [et al.] - Nor Azlan, Nazia Zulaiqha; Balqis, Nurain; Mohd Sharil, Huda Farzana; Erwan, Nur Amirah Athilah; Ismail, Nur Kiasatina Amirah; Zakaria, Nur Aina Amirah (2023)
The process of bringing a new product to market, from concept genesis to market introduction, is referred to as new product development. It includes market research, concept development, design, prototyping, testing, and commercialization. NPD strategies that are effective prioritize customer demands, promote cross-functional collaboration, and react to market conditions. In a competitive environment, timely execution, cost management, and innovation are crucial. Because of the rising emphasis on health and wellbeing, the skincare business is gaining popularity. A firm is launching a new range of revolutionary products that focus on natural and sustainable components, such as cleansers, moisturizers, serums, and specialist treatments. To assure product efficacy, the business did thorough testing and consulted with dermatologists and specialists. The company's marketing strategy focuses on openness and education, providing consumers with information about their skincare options. The firm forecasts effective market entrance and sustained expansion in the skincare area with a strong marketing approach, broad product offering, and consumer education. The problem that users face waiting between applying skincare products can be inconvenient, especially for busy people. In particular, long wait durations might also raise concerns about water-based goods evaporating. Irritation or sensitivity may occur on sensitive skin. A multi-step skincare programme with lengthy wait times might be exhausting. TripleGlow, a '3-in-1' skincare solution, tackles these concerns by providing ease and efficiency by addressing numerous skin care needs in a single application. A survey was sent to the intended respondents in order to enhance product features and commercialize it in the market. Furthermore, solid marketing strategy has been demonstrated in this research to ensure that items are accessible for commercialization in the market.